2016
DOI: 10.1074/jbc.m115.700625
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibitory Interdomain Interactions and Subfamily-specific Extensions Redefine the Catalytic Core of the Human DEAD-box Protein DDX3

Abstract: DEAD-box proteins utilize ATP to bind and remodel RNA and RNA-protein complexes. All DEAD-box proteins share a conserved core that consists of two RecA-like domains. The core is flanked by subfamily-specific extensions of idiosyncratic function. The Ded1/DDX3 subfamily of DEAD-box proteins is of particular interest as members function during protein translation, are essential for viability, and are frequently altered in human malignancies. Here, we define the function of the subfamily-specific extensions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 63 publications
6
122
0
Order By: Relevance
“…However, more recent reports have found that the mutations have inhibitory effects on mRNA translation. Specific mutations occurring in medulloblastoma were found to result in reduced RNA unwinding activity[44], defects in RNA-stimulated ATP hydrolysis[45] and hyper-assembly of RNA stress granules, which have a general inhibitory effect on translation[46]. It was proposed that inhibition of translation potentially provides a survival advantage to medulloblastoma cells during progression.…”
Section: Role Of Dead/h Box Proteins In Translating the Cancer Genomementioning
confidence: 99%
“…However, more recent reports have found that the mutations have inhibitory effects on mRNA translation. Specific mutations occurring in medulloblastoma were found to result in reduced RNA unwinding activity[44], defects in RNA-stimulated ATP hydrolysis[45] and hyper-assembly of RNA stress granules, which have a general inhibitory effect on translation[46]. It was proposed that inhibition of translation potentially provides a survival advantage to medulloblastoma cells during progression.…”
Section: Role Of Dead/h Box Proteins In Translating the Cancer Genomementioning
confidence: 99%
“…Like all DEAD-box RNA helicases, DDX3X contains a helicase core with two similar RecA-like domains that harbor 13 characteristic helicase sequence motifs, including the eponymous motif II, which reads D–E-A–D in single letter code (3, 4). The helicase core of DDX3X is flanked by an N-terminus with a nuclear export signal and regions of low sequence complexity and a C-terminus that also contains regions of low sequence complexity (Suppl.…”
Section: Introductionmentioning
confidence: 99%
“…The helicase core of DDX3X is flanked by an N-terminus with a nuclear export signal and regions of low sequence complexity and a C-terminus that also contains regions of low sequence complexity (Suppl. Fig.S1) (2, 4). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations